AI for Healthy Meal Preparation in Smart Cities - Namasivayam, Bhuvana (EAI Endorsed Transactions on Smart Cities, 2022)
INTRODUCTION: ‘Food is medicine’. Eating healthy fresh cooked foods is increasingly becoming a challenge, especially among working professionals, elderly people, people in care homes and those getting medical care, as they find it difficult to cook everyday meals and to make sure they take in all necessary nutrients regularly.OBJECTIVES: With the intervention of Robotics and AI, food preparation and delivery can be made efficient in a way it supports overall health and wellbeing.METHODS: The proposed idea is a smart city AI scheme with robots engaged in food preparation tasks such as chopping, grating etc, robotic kitchens assembled to prepare foods as per the dietary needs of various groups of people and delivery bots and drones to effectively deliver meals, fruits and necessary supplements on a daily basis and also pick up leftovers for effective waste management. This can also be extended to smart hospitals for providing nutritious meals to patients to aid in faster recovery and also avoid the carelessness and haste in food preparation when human workers are involved.
Keywords: robot; food preparation; Drone; Artificial Intelligence; Everyday meals